Pengaruh Tingkat Pengangguran Terbuka, Indeks Pembangunan Manusia, Laju Pertumbuhan PDRB Per Kapita dan Upah Minimum Provinsi Terhadap Persentase Penduduk Miskin di Indonesia pada Tahun 2021-2023 - Khasanah, Wulan Ely; Ardiantika, Annisa; Senandung Kala, Bintang; Januarta, Varrel Ega (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Poverty is a problem faced by Indonesia that affects social and economic welfare. This research aims to analyze the influence of the Open Unemployment Rate (TPT), Human Development Index (HDI), GDP Growth Rate per capita, and Provincial Minimum Wage (UMP) on the percentage poor population in Indonesia in 2021-2023. The data used is secondary data from the Central Statistics Agency (BPS) which covers 34 provinces in Indonesia. The research method uses the Common Effects Model (CEM), Fixed Effects Model (FEM), and Random Effects Model (REM) estimation models, with the Chow test and Hausman test to determine the best model. The research results show that TPT and UMP have a significant influence on the percentage of poor people, while HDI and GDP growth rate per capita are not significant. Rate and provincial minimum wages play an important role in poverty reduction efforts in Indonesia. The results of this research provide useful insights for policy makers in formulating effective strategies to improve community welfare